An Islamic Approach to Counseling for Addressing Homosexual Behavior in Adolescents - Febrianti, Audya Nursyifa; Johan, Budi; Ramadhan, Nadia Maghvira; Savitri, Hurin Nabila; Khairunnisa, Najwaa; Rahman, Zaizul Bin Ab (Al-Jadwa: Jurnal Studi Islam, 2025)
Teenage homosexuality is a challenge amid globalization and the identity struggles faced by today's youth. Islam views such behavior as a deviation from human nature that requires understanding and compassion, not punishment. This study critically evaluates the effectiveness of Islamic counseling in addressing homosexual behavior in teenagers through a review of six academic publications from 2020 to 2025. Using a literature review methodology focused on relevant journals exploring Islam-based counseling interventions, the findings indicate the effectiveness of Islamic counseling in promoting behavioral change through spiritual strengthening, self-reflection, and moral education based on the Quran and Sunnah. Findings from the literature review indicate that the structured and consistent application of Islamic counseling contributes to significant improvements in self-control and the management of individual sexual orientation. However, implementation challenges persist, including poor family communication, inadequate institutional support, and limited understanding among school counselors. This research emphasizes the importance of community, school, and family collaboration in implementing Islamic counseling as a comprehensive preventive measure. The study highlights the crucial role of spiritual approaches in helping adolescents develop healthy and appropriate sexual identity formation.